The characteristics of the curriculum for designing democratic educational environment - Korkmaz, H. Eylem; Erden, Munire (ELSEVIER SCIENCE BV, 2012)
The aim of this study is to determine the necessary characteristics that should take place in a curriculum in order to design a democratic educational environment. Delphi Technique has been used in this study. This study concludes that in a democratic educational environment the curriculum should have features which: individualize the instruction; centralize the learners' interests, needs and strengths; activate the attention of the learners in all decisions; simulate real-life situations; and promote active learning in order to gain necessary knowledge, skills and attitudes for democratic life and self-improvement. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Democratic educational environment; curriculum; Delphi technique; PROTECTION; DELPHI; Education & Educational Research